Breast Cancer in Salah Al-Deen Governorate in 2023 - Mudher Jassem, Muthanna; Ali Saad, Saad; Mustafa Al Khateeb, Huda Harith; Abedalrahman, Sarab K. (Journal of Neonatal Surgery, 2025)
Breast cancer is the commonest cancer among Iraqi females. This study aimed to identify the clinic pathological characteristics of breast cancer cases. This is a cross sectional study included 130 breast cancer patients recruited from the cancer management center in Salahdeen Governorate, Iraq, between January 1st and December 31st, 2023. Patients presented with breast lumps and underwent a triple assessment, consisting of clinical breast examination, mammography and/or ultrasonography, and fine needle aspiration cytology (FNAC). Clinical and histopathological data were collected, and staging was conducted according to the TNM classification by a surgical oncology specialist. Statistical analysis was performed using SPSS version 25. The majority of patients were housewives (81.5%), and the commonest age group was 55-65 years (28.5%). Invasive ductal carcinoma was the most prevalent histological type (89.2%), with grade III tumors being the most common (50%). Surgical intervention was performed in 81.5% of patients, with 92.5% undergoing radical mastectomy and 7.5% opting for breast-conserving surgery (BCS). Lymph node involvement was observed in 44.6% of patients, and distant metastasis was found in 36.2%. This dataset underscores the need for strategies focused on early detection, including raising awareness of breast-conserving surgery as a viable treatment option. By improving access to screenings and timely interventions, these measures can reduce the impact of advanced-stage disease and metastasis. Comparing these results with other studies emphasizes the importance of healthcare infrastructure and targeted education in improving patient outcomes.